2007
DOI: 10.1375/twin.10.6.853
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Covariation Between Autistic Traits and Behavioral Problems

Abstract: Our objective was to examine the overlap between autistic traits and other behavioral problems in a general population sample, and explore the extent to which this overlap is due to genetic or environmental factors. Youth Self Report (YSR) data were collected in a general population sample of 424 twin pairs at 18 years of age, and their nontwin siblings. In 197 of these twin families, self-report ratings on the Autism-spectrum Quotient (AQ) were collected. Stepwise backward regression analyses revealed that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 38 publications
1
26
0
1
Order By: Relevance
“…This may also have led to difficulties socializing in a female peer group, and a feeling of belonging more in a male group, thus increasing the probability of GID. Assuming AQ is relatively stable throughout life, transmen can be assumed to have had an increased number of autistic traits in early development, possibly because of elevated foetal testosterone (FT) levels (Auyeung et al 2009;2010) and/or genetic factors (Hoekstra et al 2007). Such an idea fits with research based on studies of amniotic testosterone levels that show a correlation between foetal testosterone (FT) and autistic traits (Auyeung et al 2009;2010).…”
Section: Discussionmentioning
confidence: 87%
“…This may also have led to difficulties socializing in a female peer group, and a feeling of belonging more in a male group, thus increasing the probability of GID. Assuming AQ is relatively stable throughout life, transmen can be assumed to have had an increased number of autistic traits in early development, possibly because of elevated foetal testosterone (FT) levels (Auyeung et al 2009;2010) and/or genetic factors (Hoekstra et al 2007). Such an idea fits with research based on studies of amniotic testosterone levels that show a correlation between foetal testosterone (FT) and autistic traits (Auyeung et al 2009;2010).…”
Section: Discussionmentioning
confidence: 87%
“…Two studies found modest to moderate levels of phenotypic overlap between autistic-like and anxious/depressed traits at ages 7 to 15 (Constantino et al 2003) and 18 to 19 (Hoekstra et al 2007), but did not assess the etiological relationship within a quantitative genetic model. In our previous work using the current sample, we also found a modest phenotypic correlation between global measures of autistic-like and internalizing traits at age 8 to 9 years (Hallett et al 2009a).…”
Section: Twin Studies Of Autistic-like and Internalizing Traitsmentioning
confidence: 99%
“…A number of studies have shown the relevance of dimensional representations of autism related problems in clinical and general population samples (Constantino et al 2006;Frazier et al 2010Frazier et al , 2012Mandy et al 2012;Mulligan et al 2009;Reiersen, Constantino, Grimmer, Martin, and Todd 2008) as well as their genetic independence (Constantino, Hudziak, and Todd 2003;Hoekstra, Bartels, Hudziak, van Beijsterveldt, and Boomsma 2007). From this perspective, autism-related problems constitute a general dimension of individual differences rather than a specific dimension only relevant for a subsample of patients, similar to how internalizing and externalizing problems are conceived of.…”
mentioning
confidence: 99%